Hexapole [9]Helicene. Issue 2 (12th December 2018) - Wang, Yonggen; Yin, Zhibo; Zhu, Yanpeng; Gu, Jiajian; Li, Yang; Wang, Jiaobing
Abstract: Herein we present the first hexapole [9]helicene (H9H ). Co‐catalyzed [2+2+2] cyclotrimerization of a dinaphthopyrene (DNP) functionalized alkyne provides the hexaaryl benzene precursor2, which is transformed intoH9H via a dehydrocyclization reaction. Formation of each embedded [9]helicene involves forging of a new C−C bond, which stitches together two [4]helicene subunits of the neighboring DNP blades, reminiscent of the initial method Martin developed for the preparation of [9]helicene in the 1960s. Single‐crystal X‐ray analysis of both2 andH9H discloses their extremely distorted and crowded structural features. Chiral resolution, optical and electronic properties ofH9H are also presented. Abstract : New twist : The first hexapole [9]helicene with an extremely twisted structure has been synthesized and characterized. Formation of each embedded [9]helicene (see scheme, cyan) involves forging of a new C−C bond (purple) to stitch together two [4]helicene subunits, reminiscent of the initial approach Martin developed in the 1960s to make the pristine [9]helicene.